Inovasi Penilaian Mufrodat Menggunakan Media Audio Visual Berbasis Teknologi QR Code Pada LKS Bahasa Arab - Nailis Sa'adah; M. Yunus Abu Bakar (Muróbbî: Jurnal Ilmu Pendidikan, 2025)
Assessment is part of the learning process. As time goes by 8innovation in assessment is also needed so that the objectives of learning are implemented optimally. This is no exception to the innovation of mufrodat assessment or what is also called Arabic vocabulary. Nowadays, the rapid development of technology has become the basis for innovation in learning assessment. LKS, which is one of the teaching materials for Arabic language lessons, of course contains a mufrodat assessment instrument. The existence of conventional teaching materials is certainly less attractive when presented in today's digital era education system. Therefore, the assessment of Arabic vocabulary innovates by presenting audio-visual media packaged in a QR code. So the function of the LKS itself has experienced significant innovation in learning and keeps up with the times. This research uses the library study method, which is a list of references from all types of references such as books, journal papers, articles, dissertations, theses, theses, hand outs, laboratory manuals, and other scientific works. The aim of this research is to provide information about the importance of innovation in mufrodat assessment, so that QR codes emerge as a technology that packages audio-visual learning media and worksheets in one teaching material